Using Tracking Infrastructure to Support Public Health Programs, Policies, and Emergency Response in New York City. (March 2015) - Jeffery, Nancy Loder; McKelvey, Wendy; Matte, Thomas
Abstract : Objective: To describe how the New York City (NYC) Tracking Program has used nationally mandated Secure Portal infrastructure and staff analytical expertise to support programs and inform policy. Setting: The NYC Health Department assesses, investigates, and acts on a wide range of environmental concerns to protect the health of New Yorkers. Design: Specific examples of highly effective policies or initiatives that relied on the NYC Tracking Program are described, including restaurant sanitary grade posting, rat indexing, converting boilers to cleaner-burning fuels, reducing exposure to mercury from fish and contaminated products, and responding to Superstorm Sandy. Conclusions: The NYC Tracking Program supports the Health Department in using inspectional, administrative, and health data to guide operations. Tracking has also allowed internal and external partners to use these data to guide policy development. Abstract : This study aims at describing how the New York City Tracking Program has used nationally mandated Secure Portal infrastructure and staff analytical expertise to support programs and inform policy.